Evaluation of land transportation of newborns in Türkiye (Annals of Medical Research, 2022)
Aim: In our country, the number of Neonatal Intensive Care Units (NICUs) and the quality of service has considerably increased during the last two decades. However, improvements in the safe transportation of newborns are not at the same rate, and there are many problems that need to be solved.Appropriate transport conditions should be provided to reduce neonatal mortality and morbidity. In this study, our aim was to present transportation problems in an understandable manner, to reveal solutions proposed by the addressees of these problems, and to reduce transport-related neonatal mortality and morbidity by drawing attention to this issue.Materials and Methods: As a cross-sectional descriptive study, we attempted to reach as many physicians as possible who played a relevant role in neonatal transport and invited them to respond to a Google Forms questionnaire concerning neonatal transport problems, between the 10th and 30th of April, 2022, and their responses were recorded.Results: A total of 90 participants responded to the questionnaire. Neonatal specialists were the group with the highest response rate of 54.4%. Most of the participants were employed at University Hospitals or Training and Research Hospitals (69.7%). The most frequently used transport system was the on-duty team referred by the emergency call (112) center (84%). The participants reported that they frequently encountered undesirable events during transport, and that the transport team's approach to these events was inadequate. The solution proposal chosen most often was found to be: ‘supplying vehicles with equipment similar to those used in NICUs throughout the various regions of our country with respect to population density, and ensuring that personnel employed in these vehicles are only involved in the transportation of newborns’.Conclusion: In our country, improvements in neonatal transport are urgently needed to reduce neonatal mortality and morbidity.
Keywords: Neonatal transport; Neonatal morbidity; Neonatal mortality